The Effect of Internal Control System, Corporate Social Responsibility, and Resource Use Efficiency on Sustainability Performance: Empirical Study on Food and Beverage Manufacturing Companies Listed on the Indonesia Stock Exchange - Sari, Mei; Romli, Harsi; Hertati, Lesi (Manunggal Halim Jaya, 2025)
This study analyzes the influence of internal control systems, corporate social responsibility (CSR), and resource efficiency on sustainability performance in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period. The research employs a quantitative approach with purposive sampling of 10 companies that consistently publish annual and sustainability reports. Secondary data from financial statements and sustainability reports were analyzed using multiple linear regression. The findings indicate that internal control systems positively impact sustainability performance, demonstrating that risk management and financial transparency enhance corporate sustainability. CSR also has a positive effect, suggesting that corporate social engagement strengthens business reputation. Resource efficiency significantly contributes to sustainability by optimizing energy and raw materials while reducing production waste. These three variables collectively influence corporate sustainability performance. This study recommends that companies strengthen internal control systems, enhance CSR initiatives, and optimize resource utilization to ensure business sustainability and competitiveness in the food and beverage manufacturing industry.